Relationship Between Outdoor Air Pollutant Exposure and Premature Delivery in China- Systematic Review and Meta-Analysis - Wang, Xue; Wang, Xin; Gao, Chenghua; Xu, Xiaoqian; Li, Lehui; Liu, Yan; Li, Zichao; Xia, Yuan; Fang, Xin (International Journal of Public Health, 2023)
Objective: Preterm birth (PTB) is considered as a public health problem and one of the main risk factors related to the global disease burden. This study aims to explore the influence of exposure to major air pollutants at different pregnancies on PTB.The relationship between air pollutants and PTB in China was collected from cohort studies and case-control studies published before April 30, 2022. Meta-analysis was carried out with STATA 15.0 software..A total of 2,115 papers were retrieved, of which 18 papers met the inclusion criteria. The comprehensive effect of pollutant exposure and PTB were calculated. PM2.5 during entire pregnancy and O3 exposure during third trimester were positively associated with preterm birth. Every 10 μg/m 3 increase in the average concentration of PM2.5 during the whole pregnancy will increase the risk of premature delivery by 4%, and every 10 μg/m 3 increase in the average concentration of O3 in the third trimester will increase the risk of premature delivery by 1%.Exposure to PM2.5 entire prenatal pregnancy and O3 in third trimester is associated with an increased risk of preterm birth occurrence.